2015
DOI: 10.1016/j.brainresbull.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nicotine changes the response to postnatal chlorpyrifos: Interactions targeting serotonergic synaptic function and cognition

Abstract: Nicotine and chlorpyrifos are developmental neurotoxicants that target serotonin systems. We examined whether prenatal nicotine exposure alters the subsequent response to chlorpyrifos given postnatally. Pregnant rats received nicotine throughout gestation at 3 mg/kg/day, a regimen designed to achieve plasma levels seen in smokers; chlorpyrifos was given to pups on postnatal days (PN) 1–4 at 1 mg/kg, just above the detection threshold for brain cholinesterase inhibition. We assessed long-term effects from adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 74 publications
(129 reference statements)
3
13
0
4
Order By: Relevance
“…It has been classified as a potent inhibitor of both systemic and brain cholinesterases (ChE), leading to the onset of acute neurotoxic symptomatology. However, an increasing body of reports have suggested that CPF also disrupts the serotonergic neurotransmitter system (Slotkin et al, 2015), targets serine hydrolase enzymes (Quistad et al, 2006b) and interferes with the signaling of hormones, some of which -for example, insulin and leptin-are related to energy homeostasis (Lassiter and Brimijoin, 2008;Slotkin et al, 2005). In accordance, sundry investigations have shown that CPF exposure induce a broad spectrum of effects, including metabolic disturbances (Lasram et al, 2014;Peris-Sampedro et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…It has been classified as a potent inhibitor of both systemic and brain cholinesterases (ChE), leading to the onset of acute neurotoxic symptomatology. However, an increasing body of reports have suggested that CPF also disrupts the serotonergic neurotransmitter system (Slotkin et al, 2015), targets serine hydrolase enzymes (Quistad et al, 2006b) and interferes with the signaling of hormones, some of which -for example, insulin and leptin-are related to energy homeostasis (Lassiter and Brimijoin, 2008;Slotkin et al, 2005). In accordance, sundry investigations have shown that CPF exposure induce a broad spectrum of effects, including metabolic disturbances (Lasram et al, 2014;Peris-Sampedro et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Введение никотина беременным крысам в течение всей беременности в дозе 3 мг/кг/сутки воспроиз-водило плазменные уровни типичных курильщиков; а в последующем у потомства повышалась воспри-имчивость к низким дозам хлорпирифоса (1 мг/кг) в 1-4-й дни гестации. Оценка норадренергической активности в проекции мозжечка и сопоставление следствий в коре головного мозга указывают на способность никотина при внутриутробном воздей-ствии повышать чувствительность к экологическим нейротоксикантам [176].…”
Section: пренатальные эффекты никотина на эмбриональное развитие и отunclassified
“…Недавно стали высказываться беспокойства по по-воду его возможной токсичности и необходимости запрета его использования в сельском хозяйстве и домашних условиях [186,196,212]. Развивающий-ся организм наиболее восприимчив к токсическому действию ХПФ [33,176]. У животных, пренатально подвергнутых воздействию ХПФ, в половозрелом возрасте наблюдали отдаленные нейрохимические и поведенческие нарушения [51, 62,158,170,177].…”
Section: последствия пренатального воздействия хлорорганических соедиunclassified
See 2 more Smart Citations